Aeration challenge in high BSG suspended fermentation: Impact of stirred-tank bioreactor scale. (November 2019) - Moteshafi, H.; Mousavi, S.M.; Hashemi, M.
Abstract: The high loading of lignocellulosic substrates could merge the advantages of solid-state and submerged fermentations. However, high solid loading in bioreactors could result in oxygen mass transfer complications and caused extra waste of inlet air. In this work, the effects of Brewer's Spent Grain (BSG) loading on enzyme production, oxygen transfer rate (OTR) and carbon dioxide evolution rate (CER) were investigated at 50, 75 and 100 g L −1 BSG in a 2.5-L stirred tank bioreactor. However, in small-scale bioreactor, the short contact time and inadequate mixing of bubbles in liquids affected the OTR and gas holdup negatively. Therefore, xylanase production in a 14-L vessel with 100 g L −1 BSG has been studied. In a larger bioreactor, a remarkable improvement in OTR and a significant reduction in total air consumption were recorded. Furthermore, the enzyme production per 1 L of consumed air was four times greater than 2.5-L vessels. As a result, the energy consumption for aeration was less in the larger bioreactor with high solid loading. Additionally, the residual xylan content monitoring during enzyme production has revealed that the BSG's xylan content decreased in the first 12 h of cultivation and then it remained approximately constant that probably means further xylanase induction is influenced by the concentration of BSG's hydrolysis products. Concisely, it seems that initial higher solid loading could be used as a practical alternative to solid substrate feeding during the fermentation. These findings would be useful for the fermentation of high loading lignocellulosic material in the industrial-scale bioreactor. Graphical abstract: Image 1 Highlights: High BSG loading has enhanced xylanase productivity (22.7 U mL −1 h −1 ). The xylan content of BSG as a xylanase inducer was measured during fermentation. Xylanase production in larger bioreactor has showed remarkable improvement in OTR. Air consumption fell by four in larger bioreactor with high solid loading substrate.